THE ESSENCE OF THE EARTH AS A FACTOR OF PRODUCTION AND THE PROCESS OF ITS REPRODUCTION - Shparyk, Yarema; Kundytskyy, Oleksandr (European Science, 2023)
The article provides a theoretical generalization and a new solution to the scientific problem of developing theoretical provisions and practical recommendations for improving state regulation of land reproduction as a factor of production. On the basis